2010
DOI: 10.1002/cncr.24750
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in men with localized prostate cancer treated with brachytherapy with or without neoadjuvant hormone therapy

Abstract: BACKGROUND: Discrepancies exist regarding the impact of neoadjuvant hormone therapy (NHT) on the risk of allcause mortality (ACM) in men who receive brachytherapy for localized prostate cancer. Therefore, the objective of the current study was to examine the effect of NHT on the risk of ACM in men with prostate cancer who receive with brachytherapy. METHODS: The study cohort included 2474 men with localized prostate cancer who either received NHT (N ¼ 1083) or did not receive NHT (N ¼ 1391) and brachytherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The impact of ADT on OS has not been studied well, as only 19 studies (36%) reported association of ADT and OS. Overall 16 studies found no OS benefit with ADT, however, 3 found an OS detriment with the addition of ADT to brachytherapy (39,49) and in particular in men >73y (50). …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The impact of ADT on OS has not been studied well, as only 19 studies (36%) reported association of ADT and OS. Overall 16 studies found no OS benefit with ADT, however, 3 found an OS detriment with the addition of ADT to brachytherapy (39,49) and in particular in men >73y (50). …”
Section: Discussionmentioning
confidence: 97%
“…All of these changes act to increase the risk of cardiovascular events 12 – 60 months after starting ADT (24 vs. 18% P <0.001) (48) and sudden cardiac death, by adjusted HR of 1.16 (p<.004) (40). Several studies have documented a decrease in OS in patients with localized prostate cancer treated with ADT and brachytherapy (39)(49,50). Therefore, even with short duration of only 3 months ADT can negatively impacts on quality of life, and increase morbidity and mortality (48).…”
Section: Side Effects Of Androgen Deprivation Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The adverse effects of use have been widely studied and reported. In addition to the sexual side effects of a decreased libido and impotence [6], HT has been shown to lead to insulin resistance, dyslipidemia and the development of metabolic syndrome [7][8][9].…”
mentioning
confidence: 99%